Effects of a predatory starfish on substrate colonization by a dominant mussel - Hidalgo, F.J. (2011)
The pressure exerted by consumers has generally been considered to be among the main factors affecting the structure and processes in marine communities. Here, we assessed the effects of the predatory starfish Heliaster helianthus on substrate colonization by the dominant mussel Semimytilus algosus in a rocky intertidal area of the central Peruvian coast. We conducted 3 experiments: exclusions of starfish (1) from the edge of mussel beds, (2) from areas on bare substrate and (3) from areas surrounding recruitment mediators (i.e. branched macroalgae). The exclusion of H. helianthus resulted in increased cover of S. algosus in the 3 experiments. However, the colonization of the available space by S. algosus in the absence of starfish was more evident when facilitated by recruitment mediators or by migration from the edge of mussel beds than when colonization occurred during succession starting from bare substrate. By the end of the study period, however, increased S. algosus abundance, which coincided with the end of the cold phase (La Niña) of the El Niño-Southern Oscillation, overwhelmed the effects of starfish. We suggest that periodic oceanographic fluctuations are also important in controlling community dynamics in Peruvian rocky intertidal zones, highlighting the variation in the relative importance of top-down versus bottom-up control when different temporal scales are considered. © Inter-Research 2011.